An empirical investigation on the effect of Non Audit Services on the independence of the auditors - Shukla, Meenakshi (2013)
The following research makes an attempt to understand whether the independence of the auditor’s is impacted due to the provision of Non audit services by them. Data of the FTSE 100 companies over a period of 5 years (2008 to 2012) is studied for the same. To understand this complex relation, two hypotheses are built and regression analysis is done on them.